Enzymatic upgrading of eucalypt paper-grade kraft pulp within dissolving pulp production - Cadete, Sonia Marisa Silva (2018)
Dissolving-grade pulps are commonly used for the production of cellulose derivatives and regenerated cellulose. High cellulose content, low content of non-cellulosic material, high brightness, a uniform molecular weight distribution and high cellulose reactivity are the key features that determine the quality of a dissolving pulp. The first part of this work was an optimization study regarding the application of selected enzymes in different stages of a new purification process recently developed in Novozymes for purifying an eucalypt Kraft pulp into dissolving pulp, as an alternative to the pre-hydrolysis kraft (PHK) process. In addition, a viscosity reduction was achieved by cellulase (endoglucanase) treatment in the beginning of the sequence, while the GH11 and GH10 xylanases contributed to boost the brightness of the final pulp. The second part of the work aimed at exploring different auxiliary enzyme activities together with a key xylanase towards further removal of recalcitrant hemicelluloses from a partially bleached Eucalypt Kraft pulp. The resistant fraction (ca. 6% xylan in pulp) was not hydrolysable by the different combinations of enzymes tested. Production of a dissolving pulp was successful when using a cold caustic extraction (CCE) stage in the end of the sequence O-X-DHCE-X-HCE-D-CCE. The application of enzymes improved process efficiency. The main requirements for the production of a dissolving pulp (suitable for viscose making) were fulfilled: 2,7% residual xylan, 92,4% of brightness, a viscosity within the values of a commercial dissolving pulp and increased reactivity.